2020
DOI: 10.22610/jebs.v12i2(j).2992
|View full text |Cite
|
Sign up to set email alerts
|

The Governance of State-Owned Enterprises in Africa: an analysis of selected cases

Abstract: Whilst some literature is of the view that; it is nearly impossible to cultivate good corporate governance culture in state-owned enterprises (SOEs), others believe that new strategies of implementing corporate governance systems together with political will can deliver SOEs out of their efficiency doldrums. This paper presents a scientific analysis of the contentious view on the possibility of creating efficient governance mechanisms in SOEs, explores the effective cost for governance failures in SOEs in Keny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…In addition, [25] pointed out that SOEs lack the ability to track and control the movement of vehicles and loose hundreds of dollars as regards poor fleet management practices. In the same manner, other scholars such as [26] and [27] observed that fleet management on SOEs in many African countries have in spite of good intentions generally been less efficient than private firms. [28] echoed that there is gross abuse of fleet in Tanzanian public entities since some motor vehicles are being involved in transporting unauthorized parcels, parking at drivers' houses, and in other private non authorized parking slots.…”
Section: Introductionmentioning
confidence: 66%
“…In addition, [25] pointed out that SOEs lack the ability to track and control the movement of vehicles and loose hundreds of dollars as regards poor fleet management practices. In the same manner, other scholars such as [26] and [27] observed that fleet management on SOEs in many African countries have in spite of good intentions generally been less efficient than private firms. [28] echoed that there is gross abuse of fleet in Tanzanian public entities since some motor vehicles are being involved in transporting unauthorized parcels, parking at drivers' houses, and in other private non authorized parking slots.…”
Section: Introductionmentioning
confidence: 66%
“…In South Africa, evidence in this case is how Telkom has managed to turn around by addressing the challenges it was facing as an organisation. Mutize and Tefera (2020) found Telkom to be one of the successful SOEs in Africa as a result of consistent profit after tax of more than R2.5 billion rands as from 2016. However, one has to take cognisance of the fact that, in the past, Telkom was bailed out several times by government because of under-performance (Thabane & Snyman-Van Deventer, 2018).…”
Section: State-owned Enterprisementioning
confidence: 99%
“…Past studies were fixated mostly on researching the performance of SOEs (Böwer 2017) and governance challenges in the SOEs (Chauke & Motubatse, 2020;Kanyane, 2018;Kanyane & Sambo, 2021;Kanyane & Sausi, 2015;Kikeri, 2018;Mutize & Tefera, 2020). The field of turnaround is under-researched in South Africa (Pretorius & Holtzhauzen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, the state keeps injecting them with bailouts to enable service delivery to the people (Carlson & Bussing 2020). The enormous debts that SOEs have incurred is a serious threat to the economy and most are failing to deliver products and services they are mandated to provide (Mutize & Tefera 2020).…”
Section: Problem Statementmentioning
confidence: 99%